2014
DOI: 10.1002/mats.201400015
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Network Formation in the Atom Transfer Radical Co‐Polymerization (ATRP) of Vinyl/Divinyl Monomers Using a Multifunctional Polymer Molecule Approach

Abstract: A mathematical model for the kinetics of copolymerization with crosslinking of vinyl/divinyl monomers in the presence of ARGET ATRP controllers is developed. A reaction scheme considering multifunctional polymer molecules, which results in a tridimensional problem, is proposed. Molecular weight development during the pre-gelation period is calculated using the method of moments. Flory-Stockmayer's theory is used for the post-gelation period. The ATRP solution copolymerization of methyl acrylate (MA) and ethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Simulation results showed that adding nitroxide‐type controllers to a vinyl/divinyl copolymerization system allows the production of more homogeneous polymer networks . Subsequently, Hernandez‐Ortiz et al developed a mathematical model for ATRP using the case of methyl acrylate and ethylene glycol diacrylate . Both developed models were used to obtain polymerization rate, molecular weight development, gelation point, evolution of sol and gel weight fractions, crosslink density, and copolymer composition, as well as concentrations of the species participating in the reaction mechanism.…”
Section: Other Polymerization Processesmentioning
confidence: 99%
“…Simulation results showed that adding nitroxide‐type controllers to a vinyl/divinyl copolymerization system allows the production of more homogeneous polymer networks . Subsequently, Hernandez‐Ortiz et al developed a mathematical model for ATRP using the case of methyl acrylate and ethylene glycol diacrylate . Both developed models were used to obtain polymerization rate, molecular weight development, gelation point, evolution of sol and gel weight fractions, crosslink density, and copolymer composition, as well as concentrations of the species participating in the reaction mechanism.…”
Section: Other Polymerization Processesmentioning
confidence: 99%
“…In an almost unchanged manner the problem has been considered in a series of follow-up studies [4,3,2,7,8,9]. No alterations to the original model itself were proposed, since the studies [4,3,2,7,8,9] mainly targeted the development of a new mathematical toolbox relevant to the problem at hand. Regarding gelation phenomena from a deterministic modelling point of view one may observe that it has been addressed by a relatively simple coagulation model with a multiplicative kernel.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several catalyst (re)generation ATRP methods using ppm (parts per million) levels of catalysts have been developed . For example, initiators for continuous activator regeneration (ICAR) ATRP and activators regenerated by electron transfer (ARGET) ATRP systems, in which chemical reducing agents are needed, have been extensively studied by experimental and simulation methods .…”
Section: Introductionmentioning
confidence: 99%
“…To date, several catalyst (re)generation ATRP methods using ppm (parts per million) levels of catalysts have been developed . For example, initiators for continuous activator regeneration (ICAR) ATRP and activators regenerated by electron transfer (ARGET) ATRP systems, in which chemical reducing agents are needed, have been extensively studied by experimental and simulation methods . For photo‐induced ATRP (photo‐ATRP) and electrochemically mediated ATRP (eATRP) systems, the regeneration of activator can be accomplished by photochemical and electrochemical reduction, respectively.…”
Section: Introductionmentioning
confidence: 99%